2002
DOI: 10.1259/bjr.75.895.750603
|View full text |Cite
|
Sign up to set email alerts
|

CT–MRI image fusion for delineation of volumes in three-dimensional conformal radiation therapy in the treatment of localized prostate cancer

Abstract: The objective of this study was to assess the utility of CT-MRI image fusion software and compare both prostate volume and localization with CT and MRI studies. We evaluated the differences in clinical volumes in patients undergoing three-dimensional conformal radiation therapy for localized prostate cancer. After several tests performed to ensure the quality of image fusion software, eight patients suffering from prostate adenocarcinoma were submitted to CT and MRI studies in the treatment position within an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 13 publications
6
53
0
1
Order By: Relevance
“…The changes in target volume in this study are in agreement with several other studies [2][3][4][5][6][7], which have demonstrated that outlining prostate and seminal vesicles using MRI results in smaller volumes and anatomically more accurate delineation. One study [7] has shown that outlining with MRI results in a smaller volume of rectal wall being included, potentially leading to a reduced risk of late toxicity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The changes in target volume in this study are in agreement with several other studies [2][3][4][5][6][7], which have demonstrated that outlining prostate and seminal vesicles using MRI results in smaller volumes and anatomically more accurate delineation. One study [7] has shown that outlining with MRI results in a smaller volume of rectal wall being included, potentially leading to a reduced risk of late toxicity.…”
Section: Discussionsupporting
confidence: 92%
“…MRI has reduced interference from metal implants such as prosthetic hips [2] and gold seed implants and therefore has the potential to provide improved target volume delineation over CT. Changes in anatomical and tumour definition as a result of using MRI data compared with CT have been reported for prostate [2][3][4][5][6][7], head and neck [8][9][10][11] and brain cancer [12,13] patients.…”
mentioning
confidence: 99%
“…The CT and MRI fusion was done by automated computerized fusion and then checked manually, as described in other IPL boost studies. 14,21,22 Clinical target volume (CTV) included the prostate and the entire seminal vesicles. The planning target volume for 78 Gy (PTV78) was defined as CTV with a margin of 5 mm posterior and 8 mm in other directions.…”
Section: Methodsmentioning
confidence: 99%
“…New developments including fusing MRI with other imaging modalities may help direct radiotherapy planning. [33][34][35][36] More accurate targeting may decrease morbidity by reducing dose to erectile tissue and rectum. 37,38 MRI can also be helpful in the post-treatment follow-up of …”
Section: Staging Accuracy and Indicationsmentioning
confidence: 99%